Geo-ecological evaluation of mineral, major and trace elemental composition in waste rocks, soils and sediments of a gold mining area and potential associated risks - Mohd Kusin, Faradiella; Che Awang, Nor Hayati; Syed Hasan, Sharifah Nur Munirah; Abdul Rahim, Hairiyatul Aliah; Azmin, Nurshazlin; Jusop, Shamshuddin; Kim, Kyoung-Woong (Elsevier BV, 2019)
An investigation has been undertaken on the distribution of mineral, major and trace elements in mine wastes of a gold mining area from geo-ecological perspective and its association with potential human health risks. Mine waste samples consisting of waste rocks, soils and sediments (including borrow pit, waste dump, stockpile and tailings) were collected in the vicinity of Selinsing gold mine in Malaysia. Major elements in terms of their oxide contents such as SiO2, Al2O3, Fe2O3, K2O and MgO were mainly derived from their mineralogical compositions that were dominated by quartz and muscovite (in waste rocks), kaolinite and illite (in soils) and illite and chlorite-serpentine (in mine tailings). Metallic elements (Al, Fe, Mn, Zn, Sr, Cr, Cd, Ni, Cu, Co, and Pb) were found in the range of acceptable values except for metalloid arsenic. Arsenic was found in the range of 1.84–1915 mg/kg (the highest in the waste rocks of stockpile). Geochemical assessment indicated that some locations were classified as extremely contaminated, highly enriched and having high contamination with respect to arsenic according to geo-accumulation index, enrichment factor and contamination factor. In view of ecological perspective, arsenic contamination was noticeable i.e. some samples were classified as having considerable to high potential ecological risk with respect to arsenic, while contamination with regard to all other metals were classified as having low risk. In terms of health aspect, the hazard index as indicated by the lifetime cancer risk for arsenic was found in tolerable range for regulatory purposes. Other metals possess no significant non-carcinogenic or carcinogenic risks both for adults and children. The arsenic concentrations were comparable with other mining-related sites worldwide, e.g. Spain, China, South Korea, Poland and Mongolia among others. Iron, As and Cd in the tailings and discharges from treatment facilities within the mine have been removed by 82.9–94.7%. Overall, this paper has highlighted the geo-ecological importance and implication of mining exploration to avoid ecological damages so as to sustain mining sector without inflicting the environment.